Microclimatic factors and soil characteristics of Arroceros Forest Park in the City of Manila, Philippines (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Berame JS, Elazegui EP, Arenas MC, Orozco JA. 2021. 2021. Microclimatic factors and soil characteristics of Arroceros Forest Park in the City of Manila, Philippines. Biodiversitas 22: 4956-4962. Microclimatic factors affect many ecosystem functions. However, the challenge of acquiring consistent data has impeded the quantitative assessment of the spatial heterogeneity of soil-climate in Arroceros Forest Park as an artificial urban forest park known as the last lung of the City of Manila. With this unassisted urban forest park, this study aims to determine the microclimatic factors such as light intensity, air temperature, air humidity, wind speed and direction, soil temperature, soil pH, percent organic matter, percent soil moisture and soil texture by using a sieve analysis and textural triangle method to know the status of the forest park. These procedures reveal the soil type available in the park to be clay and loam suitable for growing plants abundantly. Results showed that four microclimate factors viz. air temperature, air humidity, percent organic matter, and soil texture, were highly significant (p
Keywords: : Microenvironment, soil gap size characterizations, feel method, sieve analysis, forest dynamic, urban made forest.